Examination of Micro Vascular Density on Metastatic Colorectal Cancer of RAS Mutant-Type as Anti Vegf Therapy Predictor - Sulistyo, Heru; Budipramana, Vicky Sumarki (Folia Medica Indonesiana, 2021)
According to the NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) on Colon Cancer Version 2.2019, mCRC patients with mutant type RAS were treated with anti-VEGF. However, the use of the targeting therapy still had inconsistent results. Neoangiogenesis studies had been used as a basis to assess the prognosis of mCRC. Microvascular density (MVD) had become the morphological gold standard to assess neovascularization in human tumors. This study proved the existence of low microvascular density (MVD) in mCRC patients with mutant type RAS status as a predictor of failure of anti-VEGF therapy. There were 29 patients at Dr. Soetomo Academic Hospital from 2015-2018 who had their RAS status checked and tested for microvascular density (MVD). The results of this study were analyzed using SPSS 23.0. In the Mutant-type of RAS group, this study examined microvascular density (MVD). 11 (73%) research subjects with high MVD scores and 4 (27%) research subjects had low MVD scores. Besides, 27% microvascular density (MVD) was low, in the mutant-type of RAS mCRC patient which could be a predictor factor for the failure of anti-VEGF therapy.